Peripapillary and macular microvasculature features of non-arteritic anterior ischemic optic neuropathy - Pugazhendhi, Sangeethabalasri; Yu, Miaomiao; Zhou, Gabriella; Chen, Yuxuan; Wang, Ruikang; Liao, Yaping Joyce (Frontiers in Medicine, 2023)
Purpose The hallmark of non-arteritic anterior ischemic optic neuropathy (NAION) is vascular compromise to the anterior optic nerve and thinning of the retinal nerve fiber layer (RNFL) and secondary degeneration of the retinal ganglion cell body or thinning of the ganglion cell complex (GCC). This study investigates optical coherence tomography (OCT) and OCT Angiography (OCTA) changes in chronic NAION and identifies imaging biomarkers that best predict disease. Methods We performed a retrospective case-control study of 24 chronic NAION eyes (18 patients) and 70 control eyes (45 patients) to compare both whole-eye and regional OCT, OCTA, static perimetry measurements. OCT measurements were quantified automatically using commercial software, and OCTA was analyzed using custom MATLAB script with large vessel removal to measure 154 total parameters per eye. Results We confirmed that static perimetry mean deviation (MD) was significantly worse in chronic NAION (–13.53 ± 2.36) than control (–0.47 ± 0.72; P < 0.001) eyes, and NAION eyes had 31 μm thinner RNFL (control: 95.9 ± 25.8 μm; NAION: 64.5 ± 18.0, P < 0.001), and 21.8 μm thinner GCC compared with controls (control: 81.5 ± 4.4 μm; NAION: 59.7 ± 10.5, P < 0.001). Spearman correlation analysis of OCTA parameters reveal that vessel area density (VAD) and flux are highly correlated with visual field MD and OCT measurements. Hierarchical clustering two distinct groups (NAION and control), where standardized measurements of NAION eyes were generally lower than controls. Two-way mixed ANOVAs showed significant interaction between patient status (control and chronic NAION) and structure (optic disk and macula) for annulus VAD and flux values and mean RNFL and GCC thickness. Post-hoc tests showed this effect stems from lower peripapillary values in NAION compared to controls. Separate logistic regression models with LASSO regularization identified VAD and flux are one of the best OCTA parameters for predicting NAION. Conclusion Ischemic insult to the optic disk is more severe likely from primary degeneration of the affected peripapillary region while macula is affected by secondary retrograde degeneration and loss of retinal ganglion cells. In addition to OCT measurements, peripapillary and macular vascular parameters such as VAD and flux are good predictors of optic nerve and retinal changes in NAION.